Terapi Okupasi Pada Pasien Dengan Halusinasi Di Rumah Sakit Umum Daerah Banyumas - Jatinandya, Melinda Puspita; purwito, Dedy Purwito (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective : To determine the effects of occupational therapy in patients with hallucinations in Banyumas Regional Hospital.Method: The research method used in this study was descriptive quantitative with a cross-sectional approach. The sampling technique employed random sampling with a sample size of 32 respondents who fit the inclusion and exclusion criteria. Results: In the assessment of positive behavioral aspects, the value of p 0.0001 (p 0.05) was obtained which indicated that there was an influence on the positive behavior of respondents statistically. In the assessment of negative behavioral aspects, the p-value obtained was 0.0049 (p 0.05) which implied that there were changes in the negative behavioral aspects of the respondent statistically. In addition, in the assessment on the aspect of the patient ability, p-value 0.037 (p 0.05) was obtained which meant that there was a change statistically in the aspect of patient ability in the Sadewa ward of Regional General Hospital of Banyumas.Conclusion: In conclusion, occupational therapy effectively reduces the level of hallucinations. The change is that the patients experience a decrease in negative behavioral aspects. Moreover, the changes in positive behavioral aspects are also experienced by the patients in which they behave better. In addition, the aspect of the patient's ability is also improved to greater numbers.